Endoscopic management of duodenal perforations caused by migrated biliary plastic stents - Kim, Shin Hee; Moon, Jong Ho; Lee, Yun Nah; Lee, Tae Hoon; Woo, Sang Myung; Lee, Woo Jin; Jang, Sung Il; Lee, Dong Ki (Endoscopy International Open, 2019)
Background and study aims Duodenal perforation by migration of plastic stents placed to treat biliary lesions is rare but can be life-threatening. Surgical management is preferred, but it may increase risks of mortality and morbidity, especially in patients with underlying comorbidities and those of advanced age. We describe five cases of duodenal perforation that were successfully managed endoscopically. Four patients were elderly, and one had end-stage renal disease. We used cylindrically adapted cap-fitted endoscopy to successfully retrieve migrated plastic stents and to close the perforated walls with hemoclips. No post-procedural complication was noted. In conclusion, endoscopic management is appropriate as a first-line approach in patients with duodenal perforations caused by plastic stent migration.